Workshops em design espaços de aprendizagens e geração de conhecimentos - Fraga, Eliara dos Santos (Universidade do Vale do Rio dos Sinos, 2011)
The heightened competition unchained by the era of the information has been generating new challenges to the companies and professionals. The design is shown as a field that has been contributing to understand and act on the contemporary demands, standing out for the capacity to create value for companies and consumers. In that perspective, the study presents the investigation accomplished on a design tool - workshop, having as objective to understand the processes that happen in the Workshop in Strategic Design, implying that this instrument can be associated to learning processes and generation of knowledge. The study comprises the connection between theoretical reference and empirical research - composed by the observation of four workshops accomplished at Unisinos’ Design School, in 2009 and 2010, and six interviews made with professionals involved with Design teaching, in the same institution. The results show that the workshop in Design consists in a concentrated, intense and creative project session with a structure intentionally planned and a specific group of players, among which stand out coordinators, people that make speeches and participants. The stages (problem setting, problem solving, visualizing), that aim the problem understanding, the search for solutions and the concepts visualization, promote individual and collective reflection, connection between theory and practice, conflicts and results - that can be tangible (presented concepts) or intangible (participants experience). Therefore, the interweaving of the practical and reflexive knowledge (tacit) with the scientific and rational knowledge (explicit) of the participants turns the Workshop in Strategic Design an useful space for learning and generation of knowledge.
Keywords: Geração de conhecimento; Processos de aprendizagem; Workshops em design; Processo de projeto; Design; Generation of knowledge; Learning processes; Workshops in design; Process of project; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial